Regeneration Failure in Gulaba Forests in Himachal Pradesh:A New Perspective to This ’Forester’s Folly’ - Goraya, G. S. (Indian Forester, 2017)
The Gulaba forests in Himachal Pradesh were brought under mechanized logging from 1961-62 onwards and these logging operations continued for more than ten years. The consequential regeneration of the area , however, did not happen to the satisfaction of forest managers and has since been a cause of concern. Popularly known as "Forester’s Folly", these regeneration/plantation failures have become an embarrassment for forest managers. This paper reviews the various factors that have been for long believed to be responsible for regeneration/plantation failure in the area and brings out a new perspective to the entire issue.